Interventions for enhancing adherence to treatment in adults with bronchiectasis - McCullough, Amanda (Cochrane Database Syst Rev, 2015)
BACKGROUND: Bronchiectasis is characterised by a widening of the airways, leading to excess mucus production and recurrent infection. It is more prevalent in women and those in middle age. Many patients with bronchiectasis do not adhere to treatments (medications, exercise and airway clearance) prescribed for their condition. The best methods to change these adherence behaviours have not been identified. OBJECTIVES: To assess the effects of interventions to enhance adherence to any aspect of treatment in adults with bronchiectasis in terms of adherence and health outcomes, such as pulmonary exacerbations, health‐related quality of life and healthcare costs. SEARCH METHODS: We searched the Cochrane Airways Group Specialised Register (CAGR), which contains trial reports identified through systematic searches of CENTRAL, MEDLINE, EMBASE, CINAHL, AMED and PsycINFO, from inception to October 2015. SELECTION CRITERIA: We planned to include randomised controlled trials (RCTs) of adults with bronchiectasis that compared any intervention aimed at enhancing adherence versus no intervention, usual care or another adherence intervention. We excluded studies of those who had bronchiectasis due to cystic fibrosis. DATA COLLECTION AND ANALYSIS: Two review authors (AMcC and ET) independently screened titles, abstracts and full‐texts of identified studies. MAIN RESULTS: Searches retrieved 36 studies reported in 37 articles; no eligible studies were identified. AUTHORS' CONCLUSIONS: We did not identify any studies that assessed the effect of interventions to enhance adherence to treatment in bronchiectasis. Adequately powered, well‐designed trials of adherence interventions for bronchiectasis are needed.